Silencing cyclophilin A improves insulin secretion, reduces cell apoptosis, and alleviates inflammation as well as oxidant stress in high glucose-induced pancreatic β-cells via MAPK/NF-kb signaling pathway. Issue 1 (1st January 2020) - Li, Tangying; Quan, Huibiao; Zhang, Huachuan; Lin, Leweihua; Ou, Qianying; Chen, Kaining
ABSTRACT: Cyclophilin A is increased in the plasm of diabetic patients, while its effects on high glucose (HG)-stimulated pancreatic β-cells are still pending. The aim of this research is to investigate the effects of cyclophilin A inhibition on HG-challenged pancreatic β-cells. For investigating the effects of cyclophilin A decrease on HG-induced pancreatic β-cells, the cells were separated into normal glucose (NG), Mannitol, HG, HG + shRNA-NC, and HG + shRNA-Cyclophilin A-1 groups. The protein and mRNA expression were detected via Western blot and qRT-PCR. CCK-8 assay and flow cytometry were employed for assessing cell viability and apoptosis. The levels of oxidative stress, inflammation, and insulin secretion were detected by corresponding kits. The cyclophilin A was higher in HG group. Knockdown of cyclophilin A was able to increase insulin secretion, decrease cell apoptosis, and alleviate inflammation as well as oxidant stress in HG-treated pancreatic β-cells via MAPK/NF-kb pathway. Taken together, Cyclophilin A, highly expressed in pancreatic β-cells induced by HG, is a promising therapeutic target for diabetes. Knockdown of cyclophilin A has protective effects against HG-challenged pancreatic β-cells via regulation of MAPK/NF-kb pathway. The findings in this study provided a new strategy for diabetic treatment and paved the way for future researches on diabetes treatment. Graphical Abstract: